PERAN DAN PENGARUH AISYAH DALAM BIDANG HADITS - Umniyatul Istiqlaliyah (Dirosat : Journal of Islamic Studies, 2016)
Aisyah has more abilities in qur’anic interpretation (tafsir), prophetic traditional (hadits), theology, faith, fiqh, history, genealogy, Arabic poem and medical. But, Aisyah was known more in hadits. She was placed in fourth level of seven friends (sahabat) who explain about hadits. Aisyah could explain 2.210 hadits. It shows that Aisyah was a figure who had more intelligence and amazing understanding. One of The biggest of social services from Aisyah, especially for woman, was Umm ad-Darda.